The RBM14/CoAA-interacting, long intergenic non-coding RNA Paral1 regulates adipogenesis and coactivates the nuclear receptor PPARγ. Issue 1 (December 2017) - Firmin, François; Oger, Frederik; Gheeraert, Céline; Dubois-Chevalier, Julie; Vercoutter-Edouart, Anne-Sophie; Alzaid, Fawaz; Mazuy, Claire; Dehondt, Hélène; Alexandre, Jeremy; Derudas, Bruno; Dhalluin, Quentin; Ploton, Maheul; et al.
Abstract Adipocyte differentiation and function relies on a network of transcription factors, which is disrupted in obesity-associated low grade, chronic inflammation leading to adipose tissue dysfunction. In this context, there is a need for a thorough understanding of the transcriptional regulatory network involved in adipose tissue pathophysiology. Recent advances in the functional annotation of the genome has highlighted the role of non-coding RNAs in cellular differentiation processes in coordination with transcription factors. Using an unbiased genome-wide approach, we identified and characterized a novel long intergenic non-coding RNA (lincRNA) strongly induced during adipocyte differentiation. This lincRNA favors adipocyte differentiation and coactivates the master adipogenic regulator peroxisome proliferator-activated receptor gamma (PPARγ) through interaction with the paraspeckle component and hnRNP-like RNA binding protein 14 (RBM14/NCoAA), and was therefore called PPARγ-activator RBM14-associated lncRNA (Paral1 ).Paral1 expression is restricted to adipocytes and decreased in humans with increasing body mass index. A decreased expression was also observed in diet-induced or genetic mouse models of obesity and this down-regulation was mimickedin vitro by TNF treatment. In conclusion, we have identified a novel component of the adipogenic transcriptional regulatory network defining the lincRNAParal1 as an obesity-sensitive regulator of adipocyte differentiation and function.